2015
DOI: 10.1002/cctc.201402995
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Mesoporous Poly(ionic liquid)s towards Highly Efficient and Contamination‐Resistant Solid‐Base Catalysts

Abstract: Mesoporous poly(ionic liquid)s were synthesized by radical copolymerization of the ionic liquid 1‐aminoethyl‐3‐vinylimidazolium bromide with divinylbenzene plus the ion exchange of bromide anions with hydroxyls. Characterizations revealed the high ionic liquid content, large surface area, and hydrophobicity for the sample prepared with equimolar amounts of ionic liquid and divinylbenzene, with good accessibility to organic compounds and resistance to CO2/H2O contamination. The mesoporous copolymer behaved as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 66 publications
0
57
0
Order By: Relevance
“…In contrast, a template‐free approach greatly shortens the synthetic period and reduces the overall cost and risk involved in template‐based synthesis. Recently, it was found that direct radical copolymerization of the IL monomers (3‐alkyl‐1‐vinylimidazolium bromide) with crosslinker, divinylbenzene (DVB), gives rise to intrinsically mesoporous ILs without adding stabilizers, surfactants, hard or soft templates (Scheme ) to yield PILs of tunable BET surface area in the range of 52–649 m 2 /g. 337 The obtained PILs have been reported to show potential applications in CO 2 adsorption and catalysis after incorporation of functional anions (e.g.…”
Section: Functionalization Of Adsorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a template‐free approach greatly shortens the synthetic period and reduces the overall cost and risk involved in template‐based synthesis. Recently, it was found that direct radical copolymerization of the IL monomers (3‐alkyl‐1‐vinylimidazolium bromide) with crosslinker, divinylbenzene (DVB), gives rise to intrinsically mesoporous ILs without adding stabilizers, surfactants, hard or soft templates (Scheme ) to yield PILs of tunable BET surface area in the range of 52–649 m 2 /g. 337 The obtained PILs have been reported to show potential applications in CO 2 adsorption and catalysis after incorporation of functional anions (e.g.…”
Section: Functionalization Of Adsorbentsmentioning
confidence: 99%
“…337 The obtained PILs have been reported to show potential applications in CO 2 adsorption and catalysis after incorporation of functional anions (e.g. heteropolyanion as in Scheme ) or cations …”
Section: Functionalization Of Adsorbentsmentioning
confidence: 99%
“…, heteropolyanion in Fig. 4a)29 or cations 31. For example, functionalization of the IL monomer by an amino–alkyl chain yields a porous IL with a high surface area of 429 m 2 g –1 after ion exchange with NaOH 31.…”
Section: Template-free Synthesis Of Porous Ilsmentioning
confidence: 99%
“…Four cycles were carried out and the yields gradually decreased from 100% to 92%. A new hydrophobic mesoporous poly(ionic liquid) was used as a recyclable solid-base catalyst for solvent-free Knoevenagel condensations [29]. This material, denoted as 37, was prepared in two synthetic steps: (a) synthesis of polymer 36 by radical copolymerization of 1-aminoethyl-3-vinylimidazolium bromide hydrobromide with divinylbenzene varying the molar ratio of two monomers; (b) ion-exchange reaction with a NaOH solution (Scheme 16).…”
Section: C-c Bond Forming Reactionsmentioning
confidence: 99%